Chromatographic and massspectrometric analysis of glycosylated recombinant human insulin. - M. N. Korchaznikova; I. V. Nazimov; Yu. M. Glubokov; V. V. Bezuglov (Тонкие химические технологии)
The recombinant modified peptides and proteins method of structure and properties determination has been considered by the example of the glycosylated gene-spliced human insulin with disaccharide.